PELAKSANAAN TAKWIL DALAM TAFSIR AL-KASYSYAAF OLEH AL-ZAMAKHSYARIY - Bilfahmi Putra (Hadharah: Jurnal Keislaman dan Peradaban, 2018)
This problem is motivated by the very striking difference between al-Zamakhsyariy with other mufassir in interpreting (mentakwil) verses of the Qur'an. The subject matter is: how can the implementation of takwil that conducted by al-Zamakhsyariy in the Tafsir al-Kasysyaaf, limited by the two restrictions; how the process of practice penakwilan al-Zamakhsyariy implemented, and how the results of the form takwil. This study aims: to found the process of penakwilan by al-Zamakhsyariy, and found the form of takwil that clear. This research is library research, primary data source is al-Kasysyaaf, and secondary data source is books, journals scientific and documents related with these discussion, the methods used in this study is qualitative method and content analysis. The process of penakwilan that carried out al-Zamakhsyariy; write the verse/pronunciation that would be takwil, explained the pieces of verse which takwil from terms of grammatical science and balaghaah atau ma’aaniy, and sometimes mentawkilkan in accordance with the his mazhab (Mu'tazilah) and also contrary to the taught of his mazhab, explaining verse or pieces of verse at takwil by way of question and answer, and write the rhyme and the words of the Arabs, and explained the hadits to strengthen of the explanation, quotes the opinions of scholars earlier. While the results of penakwilan process conducted al-Zamakhsyariy is; Al-Zamakhsyariy mentawkilkan the verses mutasyaabih, and the verses or pronunciations that are contrary to the understanding of the Mu'tazilah, mentawkilkan the verses not mutasyaabih.